La cultura de la acequia madre: cleaning a community irrigation ditch - Smith, Jeffrey S.; Engel, Matthew R.; Hurt, Douglas A.; Roth, Jeffery E.; Stevens, James M. (My University, 2012)
Throughout rural New Mexico and south-central Colorado, acequias (irrigation ditches) are the lifeblood of Hispano communities. Without the water delivered by acequias, residents would face the all but impossible task of trying to farm in the region's harsh, semiarid environment. Irrigation water is vitally important to village life. From their initial construction to the equitable distribution of water, acequias bring village residents together for a common cause. Particularly important is the annual spring cleaning. Few village events are more culturally significant than la limpia de la acequia (the cleaning of the ditch). Each year residents set aside time to help repair and maintain the village waterway. As people gather, ties between family and friends are strengthened. But more importantly, the annual event plays an invaluable role in helping to shape and sustain the local culture. Through an examination of the spring cleaning of the acequia madre (mother/main ditch) in the village of El Cerrito, New Mexico, our central objective is to articulate some of the various underlying ways cultural messages are being projected and received by local residents.
Keywords: New Mexico; El Cerrito; Acequias